2013
DOI: 10.1021/am3031129
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Rectification in Boron Nitride Heterojunctions to Silicon

Abstract: Cubic and hexagonal boron nitride (cBN and hBN) heterojunctions to n-type Si are fabricated under low-energy ion bombardment by inductively coupled plasma-enhanced chemical vapor deposition using the chemistry of fluorine. The sp2-bonded BN/Si heterojunction shows no rectification, while the cBN/sp2BN/Si heterojunction has rectification properties analogue to typical p-n junction diodes despite a large thickness (∼130 nm) of the sp2BN interlayer. The current-voltage characteristics at temperatures up to 573 K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Thus, the activation energy depends dominantly upon the polarity of the voltage and little upon the magnitude of the voltage, analogue to typical p-n diodes. 17 The saturation of the activation energy at high bias voltages is attributed to a series resistance.…”
Section: Electrical Characterization Of Ncd/si Heterojunctionsmentioning
confidence: 99%
“…Thus, the activation energy depends dominantly upon the polarity of the voltage and little upon the magnitude of the voltage, analogue to typical p-n diodes. 17 The saturation of the activation energy at high bias voltages is attributed to a series resistance.…”
Section: Electrical Characterization Of Ncd/si Heterojunctionsmentioning
confidence: 99%
“…Such asymmetric cBN films are expected to present interesting rectifying effects, which is indeed supported by experimental and theoretical reports. 9,12,2428 Among them, it is worth mentioning the experimental study 28 where clear rectification in cBN/sp 2 BN/Si heterojunctions is observed. Further, the electron transport behavior is characteristic of typical p–n junction diodes over a range of temperatures varying from 298 up to 573 K. Very recently, another study on the thermal stability of BN/Si p–n heterojunction diodes was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heterostructures could exhibit remarkable electron transport properties, which are absent or not good in homostructures, such as spinfiltering effect 40,41 and current rectifying behavior. [40][41][42][43] In this study, we designed in-plane heterostructures consisting of MoS 2 and WS 2 nanoribbons and examined the electronic transport properties of two-probe devices using first-principles calculations. The electronic properties of these heterostructures were calculated through the first-principles density functional theory (DFT) combined with the non-equilibrium Green function (NEGF) method, as implemented in the Atomistix ToolKit software package.…”
Section: Introductionmentioning
confidence: 99%